Dzielenie się wiedzą oraz zaufanie w małych i średnich przedsiębiorstwach - Paliszkiewicz, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2007)
In this article problems connected with sharing of knowledge and trust have been presented. The authors have also described researches connected with this problem in polish small and medium enterprises. The research was done in Silesian Province in 2006. The questionnaire was administered to managers. The research showed that trust among employees is similar in small and medium enterprises